Chromofungin Ameliorates the Progression of Colitis by Regulating Alternatively Activated Macrophages - Eissa, Nour; Hussein, Hayam; Kermarrec, Laëtitia; Grover, Jasmine; Metz-Boutigue, Marie-Hélène Et; Bernstein, Charles N.; Ghia, Jean-Eric (Frontiers in Immunology, 2017)
Ulcerative colitis (UC) is characterized by a functional dysregulation of alternatively activated macrophage (AAM) and intestinal epithelial cells (IECs) homeostasis. Chromogranin-A (CHGA) secreted by neuroendocrine cells is implicated in intestinal inflammation and immune dysregulation. CHGA undergoes proteolytic processing to generate CHGA-derived peptides. Chromofungin (CHR: CHGA47-66) is a short CHGA-derived peptide encoded by CHGA Exon-IV and is involved in innate immune regulation, but the basis is poorly investigated. We investigated the expression of CHR in colonic tissue of patients with active UC and assessed the effects of the CHR in dextran sulfate sodium (DSS) colitis in mice and on macrophages and human colonic epithelial cells. We found that mRNA expression of CHR correlated positively with mRNA levels of AAM markers and gene expression of tight junction (TJ) proteins, and negatively with mRNA levels of interleukin (IL)-8, IL18, and collagen in patients with active UC. Moreover, AAM markers correlated positively with gene expression of TJ proteins and negatively with IL8, IL18, and collagen gene expression. Experimentally, intracolonic administration of CHR protected against DSS-induced colitis by priming macrophages into AAM, reducing colonic collagen deposition and maintaining IECs homeostasis. This effect was associated with a significant increase of AAM markers, reduction of colonic IL-18 release and conservation of gene expression of TJ proteins. In vitro, CHR enhanced AAM polarization and increased the production of anti-inflammatory mediators. CHR-treated AAM conditioned medium increased Caco-2 cell migration, viability, proliferation, and mRNA levels of TJ proteins, and decreased oxidative stress-induced apoptosis and pro-inflammatory cytokines release. Direct CHR treatments had the same effect. In conclusion, CHR treatment reduces the severity of colitis and the inflammatory process via enhancing AAM functions and maintaining IECs homeostasis. CHR is involved in the pathogenesis of inflammation in experimental colitis. These findings provide insight into the mechanisms of colonic inflammation and could lead to new therapeutic strategies for UC.